Uptake of influenza Vaccination among Health Care Workers in Federal General Hospital, Islamabad: Uptake of influenza Vaccination among Health Care Workers - Saba, AS; Khattak, Muhammad Iftikhar; Uddin, Muhammad Aleem; Asghar, Nazish; Naseem, Fatima; Rashid, Faisal (Pakistan Journal of Health Sciences, 2024)
Influenza, a highly contagious respiratory illness, imposes a substantial public health burden globally. Objectives: To identify reasons for not taking influenza vaccination shots and to explore whether healthcare workers are following any Standard operating procedure. Methods: In the present study, a structured questionnaire was employed, which was adapted from a previously published research study. This research was conducted at the Federal General Hospital located in Islamabad. The target population for this study consisted of healthcare workers employed at Federal General Hospital, Islamabad. The questionnaire was designed to gather information regarding influenza vaccination, including uptake rates, and to identify barriers and factors influencing the decision to take influenza vaccination among healthcare workers. Results: Three hundred workers were registered for the following study. About half of the participants, 47.7%, reported receiving immunizations in the past six months, which shows active participation in vaccination practices. A significant association was observed in assessing knowledge of vaccination, with 22.1% of individuals demonstrating knowledge of immunization. There was a strong association for specific knowledge (OR=2.750). No significant association was found for understanding (OR=0.482, p=2.048). No significant association was seen between barriers (OR=0.708) (p-value=1.00) Conclusions: It was concluded that established guidelines and recommendations, a notably small percentage of healthcare workers opted for influenza vaccination. To rectify this situation, comprehensive strategies are required, encompassing various elements. These strategies should include initiatives to heighten awareness regarding the significance of the influenza vaccine and align vaccination practices with international guidelines.